DETERMINANTS OF SUBJECTIVE WELLBEING: LITHUANIAN CASE - Dirzyte, Aiste; Patapas, Aleksandras (European Scientific Journal, ESJ, 2015)
This paper presents some selected results of the survey (representative sample, n=1002) which was conducted in Lithuania in 2014. This research was funded by the European Social Fund under the Global Grant measure (No. VP1-3.1-ŠMM-07-K-03-032). The study revealed various relations between Lithuanians’ wellbeing, attitudes towards life, emotional states, and suicidal ideation. The results demonstrated statistically significant negative relationship between Lithuanians’ satisfaction with life and negative emotional states: anxiety, psychological pain, sadness, hopelessness, helplessness, meaninglessness. It was found statistically significant positive relationship between Lithuanians’ satisfaction with life and positive emotional states: joy, gratefulness, enthusiasm, trust, confidence, compassion, hopefulness, happiness, peacefulness. The results have also demonstrated positive correlations between satisfaction with life and positive life perceptions: clear goals in life, perceiving life as fulfilled, worthy living, pleasant, meaningful. The results might imply that in order to diminish the rates of suicides in Lithuania, there is a need to implement evidence based psycho-educational programs and interventions.